2007
DOI: 10.1128/aem.00047-07
|View full text |Cite
|
Sign up to set email alerts
|

Coccoid Form of Helicobacter pylori as a Morphological Manifestation of Cell Adaptation to the Environment

Abstract: After characterization of preferred conditions for Helicobacter pylori survival in the sessile state, it was observed that the bacterium transforms from spiral to coccoid under mild circumstances, whereas under extreme ones it is unable to undergo shape modification. This strongly supports the view that transformation into the coccoid form is an active, biologically led process, switched on by the bacterium as a protection mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 27 publications
2
90
1
5
Order By: Relevance
“…For all water samples analyzed it was not possible to recover (1,4,33) and in biofilms exposed to water (2,14), which suggests that the difficulty of recovering cultivable H. pylori in this work was due to interactions between this microorganism and other species in the bacterial population present in water, like competition for nutrients or the production of toxic compounds by other microorganisms. However, it is also important to mention that overgrowth of other microorganisms occurred in certain samples.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…For all water samples analyzed it was not possible to recover (1,4,33) and in biofilms exposed to water (2,14), which suggests that the difficulty of recovering cultivable H. pylori in this work was due to interactions between this microorganism and other species in the bacterial population present in water, like competition for nutrients or the production of toxic compounds by other microorganisms. However, it is also important to mention that overgrowth of other microorganisms occurred in certain samples.…”
Section: Resultsmentioning
confidence: 87%
“…This is extremely relevant as the morphology of H. pylori cells has been intimately connected with viability and infection capacity. Although it has been shown previously that coccoid H. pylori cells might be dead (17,26), recent reports on the behavior of H. pylori in water have shown that coccoid cells are the manifestation of an environmentally robust type of cells that might be considered to be in the viable but noncultivable (VBNC) state (2,11,12). For H. pylori, cells in this morphological condition appear to be able to become cultivable again and cause infections when they are inoculated into mice (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En este estudio, H. pylori presentó morfología espiral, U y cocoide en forma viable y no viable. Por lo cual, se puede considerar que algunas formas cocoides o de resistencia mantienen integras las membranas, considerándolos formas viables que podrían ser potencialmente infectivas como ya sugieren otros autores (Adams et al, 2003;Azevedo et al, 2007;Gião et al, 2010).…”
Section: Discussionunclassified
“…Still, many controversies have arisen regarding the possibility of reversing bacteria from the VBNC state to the culturable state through a process called resuscitation (24). There have been reports of the possibility of converting H. pylori from the coccoid to the spiral form by stimulation and nutritional supplementation, while others deny the possibility of getting revertants of this bacterium (25)(26)(27). In mouse model studies, it has been shown that the transition into the spiral form is likely to occur in vivo because the colonization of animals with the coccoid H. pylori forms allowed researchers to isolate spiral morphotype from infected mice (28).…”
Section: H Pylori Morphological Formsmentioning
confidence: 99%